Translation of Carbon‐13 EPI for hyperpolarized MR molecular imaging of prostate and brain cancer patients. Issue 4 (30th October 2018) - Gordon, Jeremy W.; Chen, Hsin‐Yu; Autry, Adam; Park, Ilwoo; Van Criekinge, Mark; Mammoli, Daniele; Milshteyn, Eugene; Bok, Robert; Xu, Duan; Li, Yan; Aggarwal, Rahul; Chang, Susan; et al.
Abstract : Purpose: To develop and translate a metabolite‐specific imaging sequence using a symmetric echo planar readout for clinical hyperpolarized (HP) Carbon‐13 ( 13 C) applications. Methods: Initial data were acquired from patients with prostate cancer ( N = 3) and high‐grade brain tumors ( N = 3) on a 3T scanner. Samples of [1‐ 13 C]pyruvate were polarized for at least 2 h using a 5T SPINlab system operating at 0.8 K. Following injection of the HP substrate, pyruvate, lactate, and bicarbonate (for brain studies) were sequentially excited with a singleband spectral‐spatial RF pulse and signal was rapidly encoded with a single‐shot echo planar readout on a slice‐by‐slice basis. Data were acquired dynamically with a temporal resolution of 2 s for prostate studies and 3 s for brain studies. Results: High pyruvate signal was seen throughout the prostate and brain, with conversion to lactate being shown across studies, whereas bicarbonate production was also detected in the brain. No Nyquist ghost artifacts or obvious geometric distortion from the echo planar readout were observed. The average error in center frequency was 1.2 ± 17.0 and 4.5 ± 1.4 Hz for prostate and brain studies, respectively, below the threshold for spatial shift because of bulk off‐resonance. Conclusion: This study demonstrated the feasibility of symmetric EPI to acquire HP 13 C metabolite maps in a clinical setting. As an advance over prior single‐slice dynamic or single time point volumetric spectroscopic imaging approaches, this metabolite‐specific EPI acquisition provided robust whole‐organ coverage for brain and prostate studies while retaining high SNR, spatial resolution, and dynamic temporal resolution.